Lao Economic Monitor, May 2016 : Challenges in Promoting More Inclusive Growth and Shared Prosperity - Najdov, Evgenij; Phimmahasay, Keomanivone (World Bank, Washington, DC, 2016)
The Lao economy is estimated to have expanded by around 7 percent in 2015, a slight moderation from 7.5 percent in 2014. Similar to the last decade, the resource sectors (hydropower and extractives) continued to make an important contribution to growth. Power generation got a boost from the commissioning of the first two blocks of the 1,878 MW Hongsa lignite power plant and an additional 250-300 MW of installed capacity in the hydro sector. Furthermore, despite lower global commodity prices, mining output still increased as metal prices remained above the mines’ cost recovery levels. The revised State Budget Law, approved in December 2015, enhances the authority of the National Assembly in budget oversight and Ministry of Finance in budget management. In addition, with regards to anti-money laundering and counter-terrorism financing, the Government strengthened key regulations (including on forfeiture of assets, border declaration, penalties for non-compliant entities) recommended by the Financial Action Task Force (FATF), which helped remove Lao PDR from the FATF’s list of ‘jurisdictions not making sufficient progress’. The outlook will depend on the progress in the implementation of the recommendations and agreed measures. GDP is expected to expand at around 7 percent per annum as a healthy pipeline in the power sector keeps investments strong and increases electricity production and exports by almost 40 percent. Stabilization of growth rates in China and some acceleration in Vietnam and Thailand should increase demand for Lao PDR exports. On the other hand, some gradual fiscal consolidation is expected, largely through broadening the revenue base and efforts to improve efficiency in spending and should help strengthen the outlook for public debt sustainability and lower the risk of debt distress from its current level of moderate, but borderline to high.